Pengaruh Ekuitas Merek Dan Kinerja Perusahaan Terhadap Risiko Perusahaan Yang Terdaftar Di Indeks LQ45 - Dwi Dewisri Kinasih; Fitri Ayu Nofirda (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
This study aims to examine the effect of brand equity and company performance on company risk. This study uses two models of corporate risk measurement, namely by using the standard deviation of Return on Assets and the standard deviation of Return on Equity. This study uses panel data regression with random effects model and data processing using Stata 14 software. The findings from this study indicate that brand equity has a positive and significant effect on company risk as measured by using the standard deviation of return on equity. While the company's performance proved to have a negative and significant effect on the company's risk.